Burden, clinical presentation and risk factors of advanced HIV disease in pregnant Mozambican women - Tacilta Nhampossa; Raquel González; Arsenio Nhacolo; Laura Garcia-Otero; Llorenç Quintó; Maura Mazuze; Anete Mendes; Aina Casellas; Gizela Bambo; Aleny Couto; Esperança Sevene; Khátia Munguambe; et al. (BMC, 2022)
Abstract Background Information on the frequency and clinical features of advanced HIV disease (AHD) in pregnancy and its effects on maternal and perinatal outcomes is limited. The objective of this study was to describe the prevalence and clinical presentation of AHD in pregnancy, and to assess the impact of AHD in maternal and perinatal outcomes in Mozambican pregnant women. Methods This is a prospective and retrospective cohort study including HIV-infected pregnant women who attended the antenatal care (ANC) clinic at the Manhiça District Hospital between 2015 and 2020. Women were followed up for 36 months. Levels of CD4 + cell count were determined to assess AHD immune-suppressive changes. Risk factors for AHD were analyzed and the immune-suppressive changes over time and the effect of AHD on pregnancy outcomes were assessed. Results A total of 2458 HIV-infected pregnant women were enrolled. The prevalence of AHD at first ANC visit was 14.2% (349/2458). Among women with AHD at enrolment, 76.2% (260/341) were on antiretroviral therapy (ART). The proportion of women with AHD increased with age reaching 20.5% in those older than 35 years of age (p < 0.001). Tuberculosis was the only opportunistic infection diagnosed in women with AHD [4.9% (17/349)]. There was a trend for increased CD4 + cell count in women without AHD during the follow up period; however, in women with AHD the CD4 + cell count remained below 200 cells/mm3 (p < 0.001). Forty-two out of 2458 (1.7%) of the women were severely immunosuppressed (CD4 + cell count < 50 cells/mm3). No significant differences were detected between women with and without AHD in the frequency of maternal mortality, preterm birth, low birth weight and neonatal HIV infection. Conclusions After more than two decades of roll out of ART in Mozambique, over 14% and nearly 2% of HIV-infected pregnant women present at first ANC clinic visit with AHD and severe immunosuppression, respectively. Prompt HIV diagnosis in women of childbearing age, effective linkage to HIV care with an optimal ART regimen and close monitoring after ART initiation may contribute to reduce this burden and improve maternal and child survival.